DIGITAL MARKETING STRATEGY FOR MSME SALES - Amelia, Nitya; Prasojo, Bayu Hari; Racmadany, Andry; Pebrianggara , Alshaf (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Digital marketing strategies play a crucial role in increasing the sales of micro, small, and medium enterprises (MSMEs) in Indonesia, especially in the rapidly evolving era of digitalization. This study aims to analyze the impact of digital marketing strategies, such as the use of social media, paid advertising, SEO (Search Engine Optimization), content marketing, and digital payment methods, on MSME performance. Method: The research employs a qualitative approach through a literature review based on relevant research articles. Results: The findings indicate that social media and paid advertising significantly contribute to expanding market reach and enhancing direct consumer interaction. SEO, although requiring more time to achieve optimal results, positively impacts the online visibility of MSMEs. Meanwhile, content marketing has a relatively lower impact, likely due to limited resources or expertise in creating effective content. The use of digital payment methods simplifies transactions and enhances the customer experience. Socio-psychological factors and credibility are also identified as critical elements in digital marketing communication strategies. Novelty: With the significant potential of MSMEs in Indonesia, optimizing digital marketing strategies can support business growth and competitiveness in the digital marketplace. This study recommends further exploration to identify other digital marketing strategies that have not been thoroughly examined.